Penatalaksanaan Fisioterapi Pada Drop Hand Dextra Di RSUD Salatiga - Kurniawan, Fajar, Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background : Drop Hand is a symptom of the radial nerve disorders that can lead to the inability of all the wrist extensor muscle group , fingers and forearm supinator . Objective : To investigate the implementation of physiotherapy in reducing pain , increasing range of motion and increase muscle strength in case of a drop hand with modalities Infra Red ( IR ) , Transcutaneus Electrical Nerve Stimulation ( TENS ) and exercise therapy ( TL ). Results : After treatment for 6 times the obtained results of the assessment of pain in silent pain T1 : 0 becomes T6 : 0 , pain motion T1 : 0 becomes T6 : 0 , tenderness T1 : 5 to T6 : 3 , increase range of motion S : T1 : 10 -0- 40 , became T6 : -0- 15 45 , F : T1 : 10 -0- 10 , became T6 : 15 -0- 15 , an increase in muscle strength of the dorsal flexion T1 : 3 , becomes T6 : 3.5 , palmar flexion T1 : 3 , becomes T6 : 3.5 , radial deviation T1 : 3 , into T6 : 3 , ulnar deviation T1 : 3 , into T6 : 3. Conclusion : Infra Red ( IR ) , Transcutaneus Electrical Nerve Stimulation ( TENS ) and exercise therapy ( TL ) can reduce pain , increase range of motion and increase muscle strength.